Silylation of mechanically ground kaolinite. (September 2014) - Tao, Q.; Su, L.; Frost, R.L.; Zhang, D.; Chen, M.; Shen, W.; He, H.
Abstract: Silylated kaolinites were synthesized at 80°C without the use of inert gas protection. The method presented started with mechanical grinding of kaolinite, followed by grafting with 3- aminopropyltriethoxysilane (APTES). The mechanical grinding treatment destroyed the ordered sheets of kaolinite, formed fine fragments and generated broken bonds (undercoordinated metal ions). These broken bonds served as new sites for the condensation with APTES. Fourier transform infrared spectroscopy (FTIR) confirmed the existence of −CH2 from APTES. 29 Si cross-polarization magic-angle spinning nuclear magnetic resonance spectroscopy ( 29 Si CP/MAS NMR) showed that the principal bonding mechanism between APTES and kaolinite fitted a tridentate silylation model (T 3 ) with a chemical shift at −66.7 ppm. The silane loadings of the silylated samples were estimated from the mass loss obtained by TG-DTG curves. The results showed that the 6-hour ground kaolinite could be grafted with the most APTES (7.0%) using cyclohexane as solvent. The loaded amount of APTES in the silylated samples obtained in different solvents decreased in the order as: nonpolar solvent > polar solvent with low dielectric constant (toluene) > polar solvent with high dielectric constant (ethanol).